Contemporary Patterns of Spontaneous Labor With Normal Neonatal Outcomes - Zhang, Jun (2010)
OBJECTIVE: To use contemporary labor data to examine the labor patterns in a large, modern obstetric population in the United States. METHODS: Data were from the Consortium on Safe Labor, a multicenter retrospective study that abstracted detailed labor and delivery information from electronic medical records in 19 hospitals across the United States. A total of 62,415 parturients were selected who had a singleton term gestation, spontaneous onset of labor, vertex presentation, vaginal delivery, and a normal perinatal outcome. A repeated-measures analysis was used to construct average labor curves by parity. An interval-censored regression was used to estimate duration of labor stratified by cervical dilation at admission and centimeter by centimeter. RESULTS: Labor may take over 6 hours to progress from 4 to 5 cm and over 3 hours to progress from 5 to 6 cm of dilation. Nulliparas and multiparas appeared to progress at a similar pace before 6 cm. However, after 6 cm labor accelerated much faster in multiparas than in nulliparas. The 95(th) percentile of the 2(nd) stage of labor in nulliparas with and without epidural analgesia was 3.6 and 2.8 hours, respectively. A partogram for nulliparas is proposed. CONCLUSION: In a large, contemporary population, the rate of cervical dilation accelerated after 6 cm and progress from 4 to 6 cm was far slower than previously described. Allowing labor to continue for a longer period before 6 cm of cervical dilation may reduce the rate of intrapartum and subsequent repeat cesarean deliveries in the United States.